From Manomin to ‘Wild’ Rice and Back Again: Understanding the Transformations of a Native Ontario Grain and Indigenous Cultural Resurgence - Dowsley, Martha; Loukes, Keira; Taylor-Hollings, Jill; Beaver, Jeff (2024)
Manomin (also called manoomin) is a native Canadian grain (Zizania palustris) that was the main carbohydrate food for many Indigenous people in Ontario for many generations and over a million pounds were harvested per year in the 20th century. However, changes to the landscape, especially the construction of dams, have destroyed much of the habitat of this plant. This project is a knowledge synthesis of the archaeological evidence and ethnohistorical information about manomin in Ontario, along with an introduction to the cultural traditions and local histories of partner First Nations. It serves as a starting point for further investigations into the relationship between people and manomin in Ontario. The main applied conclusion was that water level management in Ontario needs to include Indigenous governance for the support of manomin growth. This report was funded by the Social Sciences and Humanities Research Council of Canada and conducted in in partnership with Obishikokaang (Lac Seul First Nation) and members of Alderville First Nation in Ontario. Social Sciences and Humanities Research Council in partnership with Canadian Heritage